Short-term Outcomes of Preterm Infants in a Medical Center at Banyumas Regency, Indonesia: A Preliminary Study - Purwandari, Haryatiningsih; Huang, Mei-Chih (Babali Publisher, 2020)
Introduction: Short-term outcomes of preterm infants refers to any preterm infants’ conditions after birth including medical diagnosis or morbidity, length of stay at the hospital, and readmission to hospital after discharge. A high number of preterm births were identified as the major case in the year of 2015 in a medical center at Banyumas Regency, Indonesia. However, limited evidence showed the preterm infants’ short-term outcomes in this medical center. This study was intended to investigate the short-term outcomes of preterm infants in a medical center, Banyumas Regency, Indonesia. Methods: The study used a retrospective design with a case-control study involving a convenience sampling of data set from 50 preterm and 50 term infants who were born from January to December 2015 in a medical center, Banyumas Regency, Indonesia. Any preterm infants’ outcomes from the hospital medical record were collected. Chi-Square, T-test, and Mann-Whitney U were used for statistical analysis. Results: The study showed that preterm infants experienced low birth weight (LBW), respiratory distress syndrome (RDS), jaundice, and longer length of stay at the hospital compared to term infants (p<0.01; p=0.027; p<0.01; p<0.01, respectively). Surprisingly, the study found there was no significant difference in readmission to the hospital between two groups. Conclusion: Healthcare professionals can use the data as considerations for improving preterm infants’ optimal care.